Current Hypotheses on How Microsatellite Instability Leads to Enhanced Survival of Lynch Syndrome Patients - Kristen M. Drescher; Poonam Sharma; Henry T. Lynch (Clinical and Developmental Immunology)
High levels of microsatellite instability (MSI-high) are a cardinal feature of colorectal tumors from patients with Lynch Syndrome. Other key characteristics of Lynch Syndrome are that these patients experience fewer metastases and have enhanced survival when compared to patients diagnosed with microsatellite stable (MSS) colorectal cancer. Many of the characteristics associated with Lynch Syndrome including enhanced survival are also observed in patients with sporadic MSI-high colorectal cancer. In this review we will present the current state of knowledge regarding the mechanisms that are utilized by the host to control colorectal cancer in Lynch Syndrome and why these same mechanisms fail in MSS colorectal cancers.